Synthesis of Pt nanoparticles and their burrowing into Si due to synergistic effects of ion beam energy losses - Kumar, Pravin; Singh, Udai Bhan; Mal, Kedar; Ojha, Sunil; Sulania, Indra; Kanjilal, Dinakar; Singh, Dinesh; Singh, Vidya Nand (Beilstein Journal of Nanotechnology, 2014)
We report the synthesis of Pt nanoparticles and their burrowing into silicon upon irradiation of a Pt–Si thin film with medium-energy neon ions at constant fluence (1.0 × 1017 ions/cm2). Several values of medium-energy neon ions were chosen in order to vary the ratio of the electronic energy loss to the nuclear energy loss (Se/Sn) from 1 to 10. The irradiated films were characterized using Rutherford backscattering spectroscopy (RBS), atomic force microscopy (AFM), scanning electron microscopy (SEM), X-ray diffraction (XRD) and high resolution transmission electron microscopy (HRTEM). A TEM image of a cross section of the film irradiated with Se/Sn = 1 shows ≈5 nm Pt NPs were buried up to ≈240 nm into the silicon. No silicide phase was detected in the XRD pattern of the film irradiated at the highest value of Se/Sn. The synergistic effect of the energy losses of the ion beam (molten zones are produced by Se, and sputtering and local defects are produced by Sn) leading to the synthesis and burrowing of Pt NPs is evidenced. The Pt NP synthesis mechanism and their burrowing into the silicon is discussed in detail.
Keywords: atomic force microscopy; burrowing of nanoparticles; medium-energy ion irradiation; nuclear and electronic energy loss; Rutherford backscattering spectroscopy; scanning electron microscopy; thin films; transmission electron microscopy